2008
DOI: 10.1086/591415
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Decline Law of Classical Novae. III. GQ Muscae 1983

Abstract: We present a unified model of infrared (IR), optical, ultraviolet (UV ), and X-ray light curves for the 1983 outburst of GQ Muscae (Nova Muscae 1983) and estimate its white dwarf (WD) mass. Based on an optically thick wind model of nova outbursts, we model the optical and IR light curves with free-free emission, and the UV 1455 8 and supersoft X-ray light curves with blackbody emission. The best-fit model that simultaneously reproduces the IR, optical, UV 1455 8, and supersoft X-ray observations is a 0:7 AE 0:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(87 citation statements)
references
References 64 publications
6
81
0
Order By: Relevance
“…The nova is a known super soft X-ray source (Schwarz et al 2011, and references therein). Hachisu et al (2008) estimate the mass of the white dwarf in the system to be 0.7 ± 0.05 M . A spectrum of the remnant, obtained in 1994, is A119, page 6 of 24 shown by Diaz et al (1995).…”
Section: Gq Musmentioning
confidence: 97%
“…The nova is a known super soft X-ray source (Schwarz et al 2011, and references therein). Hachisu et al (2008) estimate the mass of the white dwarf in the system to be 0.7 ± 0.05 M . A spectrum of the remnant, obtained in 1994, is A119, page 6 of 24 shown by Diaz et al (1995).…”
Section: Gq Musmentioning
confidence: 97%
“…Mass measurements of astronomical objects are notoriously difficult and highly uncertain, but are still worth considering. Most of our mass measurements come from a series of light curve model papers by I. Hachisu and M. Kato [Hachisu & Kato(2004), Hachisu & Kato(2005), Hachisu & Kato(2006), , Hachisu et al(2008b), Hachisu et al(2008a), ), Hachisu & Kato(2010, Kato & Hachisu(2003), , , Kato & Hachisu(2011)]. In our time-limited sample, we have 27 CNe with M WD measurements, and of those 27, seven have M WD ≥ 1.2M , for 26%.…”
Section: Characteristics Of Recurrent Novaementioning
confidence: 99%
“…Similar values were reported by Krautter et al (1984) and Hassall et al (1990), who found E(B − V ) = 0.45 and 0.50, respectively, on the basis of the 2175 Å feature in the early IUE spectra. Hachisu et al (2008) obtained E(B − V ) = 0.55 ± 0.05 on the basis of the 2175Å feature and various line ratios. redetermined the color excess to be E(B − V ) = 0.45 ± 0.05 by fitting the general tracks with that of GQ Mus in the UBV color-color diagram.…”
Section: V705 Cas 1993mentioning
confidence: 99%
“…As far as the free-free emission dominates the continuum spectra, we can expect that novae follow the universal decline law. Even if there are wavy-structured or dust-blackout shapes, the overall light curves follow the universal decline law (e.g., , 2010Hachisu et al 2008; ). On the other hand, if photospheric emission dominates the nova continuum spectra, light curves do not follow the universal decline law.…”
Section: Analysis On Various Light Curve Shapes Of Classical Novaementioning
confidence: 99%
See 1 more Smart Citation